Pharmacoresistant Convulsions and Visual Hallucinations around Two Weeks after Selegiline Overdose: A Case Report - Kobayashi, T.; Saito, N.; Suda, S.; Shioda, K.; Kato, S. (Pharmacopsychiatry, 2011)
A case of pharmacoresistant convulsions after selegiline overdose is reported. A 50-year-old male having been suffering from bipolar II disorder for 16 years attempted suicide by taking an overdose of 195 mg selegiline with other psychotropics. He developed recurrent pharmacoresistant seizure from 12th day to 19th day after selegiline overdose. He also had visual hallucinations and temporary high blood pressure. The authors suspect that the catecholamine-influenced convulsions and visual hallucinations that manifested during the period increased by the MAO-inhibiting action of selegiline which lasts about 2 weeks.
Keywords: selegiline; overdose; convulsion